Pengakuan Bersalah dalam Pembaruan Hukum Acara Pidana: Antara Efisiensi Proses Peradilan dan Perlindungan Hak Terdakwa - Gregorius Widiartana (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study aims to identify and analyze the regulation of guilty pleas within the reform of criminal procedure law, as well as to identify and analyze its implications for the criminal justice system in Indonesia. This research employs normative legal research with a descriptive approach. The approaches used include statutory and conceptual approaches. The types and sources of legal materials consist of primary and secondary legal materials. The data collection technique is conducted through a literature study. The data analysis technique used is qualitative analysis. The results of this study indicate that the guilty plea mechanism in the reform of criminal procedure law is not entirely identical to the concepts of guilty plea or plea bargaining, but rather constitutes a hybrid model that maintains the active role of judges in the evidentiary process. The implications of this regulation show the potential to enhance judicial efficiency; however, it also poses risks to the protection of defendants’ rights and indicates a possible shift from the principle of material truth toward a more procedural form of resolution. Therefore, more comprehensive regulation and effective oversight are required to maintain a balance between efficiency and justice within the criminal justice system in Indonesia.